Pseudoclavibacter otitis media in a 3-year-old boy with pulmonary and spinal tuberculosis - Satja Issaranggoon Na Ayuthaya (2018)
Copyright © 2015 Wolters Kluwer Health, Inc. All rights reserved. Pseudoclavibacter has rarely been documented as an etiologic agent of infection in humans. We presented the first case report of Pseudoclavibacter otitis media in a boy with pulmonary and spinal tuberculosis. A 3-year-old boy was referred to our hospital due to prolonged fever and progressive paraplegia for 3 months. He had yellowish discharge from both ear canals. The pleural fluid culture was positive for Mycobacterium tuberculosis. The discharge from both ears culture yielded yellow colonies of gram-positive bacilli with branching. This organism was positive for modified acid-fast bacilli stain but negative for acid-fast bacilli stain. Biochemical characteristics of this isolate were positive for catalase test but negative for oxidase, nitrate, esculin, and sugar utilization tests. The organism was further subjected to be identified by 16S ribosomal deoxyribonucleic acid gene sequencing. The result yielded Pseudoclavibacter species (99.4% identical), which could be most likely a potential pathogen in immunocompromised host like this patient. He responded well with intravenous trimetroprim-sulfamethoxazole for 6 weeks. This is the first case report of Pseudoclavibacter otitis media in children, and this case could emphasize Pseudoclavibacter species as a potential pathogen in immunocompromised host.